2015
DOI: 10.1097/cmr.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600 mutations and pathological features in Japanese melanoma patients

Abstract: Ultraviolet radiation is a risk factor for BRAF V600 mutations frequently found in melanomas that cause constitutive BRAF activation. Primary sites of melanoma and the frequency of BRAF mutations might differ between races. Melanoma is rare in Japan (1500–2000 cases/year compared with 132 000/year worldwide) and the frequency and distribution of BRAF V600 mutations are unknown. We aimed to investigate the frequency of BRAF V600 mutations in a cohort of Japanese patients with melanoma and determine the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
5
31
1
Order By: Relevance
“…This is consistent with literature reports that younger age and reduced Breslow thickness are associated with the BRAF V600E mutation 54. A number of studies have shown that superficial spreading melanomas (SSM) have a higher rate of BRAF V600 mutation than other melanoma subtypes 22 55. In our study, we too observed this, with 40% of SSM samples positive for the V600E mutation; however, the result was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with literature reports that younger age and reduced Breslow thickness are associated with the BRAF V600E mutation 54. A number of studies have shown that superficial spreading melanomas (SSM) have a higher rate of BRAF V600 mutation than other melanoma subtypes 22 55. In our study, we too observed this, with 40% of SSM samples positive for the V600E mutation; however, the result was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Dabrafenib and vemurafenib, both BRAF inhibitors, have shown improved progression-free and overall survival in patients with metastatic melanoma harbouring a BRAF V600 mutation 22 25–27. A similar improvement in patient survival has been reported with the use of the MEK inhibitor trametinib, which acts downstream of BRAF in the MAPK pathway 28.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in BRAF have been noted in 50% of Caucasian patients, but in only 30–40% of Japanese patients . This difference is consistent with the fact that BRAF mutations are more frequently detected in superficial spreading melanoma (SSM), but are rarely detected in ALM …”
Section: Introductionsupporting
confidence: 87%
“…Gain‐of‐function mutations of BRAF (a signal transducer for a number of growth factor receptors) were shown to be of significance in a significant proportion of human cancer by Davies et al in 2002 . Subsequent studies suggest that BRAF mutations are present in 40%‐60% of melanoma . The most common mutant form of BRAF (B‐raf proto‐oncogene, serine/threonine kinase) in human cancer is BRAF V600E, which accounts for over 90% of BRAF mutations in melanoma .…”
Section: Introductionmentioning
confidence: 99%